1999
DOI: 10.1177/000313489906500113
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postherniorrhaphy Urinary Retention with Prazosin

Abstract: Urinary retention that necessitates catheterization after herniorrhaphy is a well known, but usually ignored, situation. Increased sympathetic activity resulting from surgery may be the contributing factor. Blockade of a receptors in the bladder neck and urethral sphinchter may prevent postoperative urinary retention. In this prospective placebo-controlled study, the efficacy of prazosin in preventing postoperative urinary retention after herniorrhaphy was investigated in 156 patients. Patients were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…13 Prazosin was also investigated in another randomized controlled trial in which 156 patients underwent elective herniorrhaphy and were randomly assigned to receive perioperative prazosin or placebo. 15 The authors found that 3.5% of patients who received the study drug developed POUR compared with 25% of patients in the placebo group (p < 0.05).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…13 Prazosin was also investigated in another randomized controlled trial in which 156 patients underwent elective herniorrhaphy and were randomly assigned to receive perioperative prazosin or placebo. 15 The authors found that 3.5% of patients who received the study drug developed POUR compared with 25% of patients in the placebo group (p < 0.05).…”
Section: Discussionmentioning
confidence: 95%
“…5 One theorized cause of POUR is the activation of alpha adrenergic receptors in the bladder neck and proximal urethra. [13][14][15][16][17][18] This hypothesis is supported by the observation that some anesthetic agents are alpha adrenergic agonists. Patients treated with these agents, including ephedrine and phenylephrine, have increased risk of developing POUR.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The incidence of POUR following IHR in other studies has varied substantially, with incidence rates of 1.4% to 22.2% reported after minimally invasive IHR; 0.7% to 38% following open IHR; and 0.8% to 13% in mixed cohorts . This wide variation may reflect heterogeneity in both practice and data recording.…”
Section: Discussionmentioning
confidence: 97%
“…Chapman et al reported that tamsulosin was effective in preventing POUR following female pelvic reconstructive surgery (Lose and Lindholm, 1985;Chapman et al, 2021). Similarly, Gönüllü et al found that prophylactic administration of prazosin could reduce the incidence of POUR and catheterization following herniorrhaphy (Gönüllü et al, 1999).…”
Section: Introductionmentioning
confidence: 99%